Successful Management of Cervical Ectopic Pregnancy: A Case Report - Laya Shirinzadeh; Amir Hosein Jafarian; Behrouz Davachi; Leila Mousavi Seresht; Helena Azimi; Samaneh Akbarzadeh; Yasaman Nikooiyan; Zohreh yousefY (Mashhad University of Medical Sciences, 2020)
Background: Cervical ectopic pregnancy is a rare condition with an incidence of less than 0.1% in all ectopic pregnancies. This life-threatening condition is associated with a high morbidity and mortality rates. Recently, the recommended protocol for the treatment of cervical ectopic pregnancy is fertility preservation rather than invasive surgery and hysterectomy. The aim of this report was to introduce a case of successful management of cervical ectopic pregnancy. Case report: A 31-year-old woman was presented with her third pregnancy with a history of one cesarean section and spontaneous abortion. She was admitted to an academic hospital with vaginal bleeding following 10 weeks of amenorrhea. Based on transvaginal ultrasound, a live fetus of about nine weeks was reported, located in the cervical canal. The β-subunit of human chorionic gonadotropin (βhCG) titer was reported as 108000 mIU/m. Cervical pregnancy diagnosis was consistent. In order to preserve fertility based on the patient's hemodynamic status, medical treatment and surgical intervention, including methotrexate and then intravaginal ligation of cervical branches of uterine arteries, and subsequently cervical tampon was successfully performed. Conclusion: The early detection and accurate diagnosis of cervical ectopic pregnancy using ultrasound and serial βhCG titer can be a valuable approach. Appropriate and conservative management has decreased the morbidity rate and preserved the ongoing fertility in the affected patients.